Development of A Risk Management System To Reduce The Impact of Cyber Threats - Rafi Farizki; Frasciskus Antonius Alijoyo (Publikasi Indonesia, 2024)
Cyber threats are one of the main issues in the digital era. Cyberattacks can result in financial, reputational and even operational disruption for organizations. In an effort to overcome this, organizations need to have an effective risk management system to identify, assess and manage cyber risks. The aim of this research is to determine the effectiveness of a risk management system that can help organizations reduce the impact of cyber threats. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that developing an effective risk management system is an important step for organizations in reducing the impact of cyber threats. A good risk management system can help organizations protect information assets, increase cyber resilience, and build customer trust.